Effect Of Leech Therapy On TEP (Thrombosed External Pile): A Case Study - Sharma, Monika (International Research Journal of Ayurveda & Yoga, 2022)
The Thrombosed external pile is the one which is located distal to the dentate line and develop as a result of tortuosity and distension of External Hemorrhoidal venous system. The engorgement of a hemorrhoidal vessel with acute swelling may allow blood to pool and subsequently clot; this leads to the Acute Thrombosed External Pile mass, a bluish purplish discolored swelling with severe pain and tenderness. The present case is of TEP (Thrombosed external pile) and the effect of Leech application is evaluated on this. The main objective is to assess the effective role of Leech on essential parameters of the patient, that are troublesome sign and symptoms - Pain, edema, tenderness and discoloration. The case is successfully managed with Leech therapy. Hirudin, calin, Factor Xa present in the saliva of Leech helps in oppressing the process of blood clot in an External pile mass and provides a symptomatic relief to the patient.